Objetivos de desenvolvimento do milênio da ONU: redução da mortalidade na infância e saneamento básico urbano no estado do Pará - VINAGRE, Marco Valério de Albuquerque (2006)
Sanitation and health are inseparable. Under this premise, is conducted the investigation contained in this study, that looks for to contribute offering to the society a new interdisciplinary point of view in the formulation and accompaniment of the public politics of urban sanitation. The use of urban indicators is improvement factor in the planning and administration of the cities, and matter up to date. There is abundance of them, however this study search the cognitive simplicity, although without reductionism, and there the concern resides with the Interdisciplinarities contained in the approach of this investigation, that culminates with the proposition of econometric model relating social and sanitary data censes. They are studied the relationships among mortality in the childhood, urban population, provision of urban services of water supply, sanitary exhaustion and waste collects. The explanatory relationships are verified among dependent's variable constituted by the product mortality in the childhood x urban population and the variables independent urban populations assisted with water supply, sewerage system and garbage collect. Considered the expressed politics of investments in sanitation in the General Budget of the State of Pará for the year of 2006 as usual, and starting from the developed model, the mortality in the childhood is inferred for the year of 2015, and compared with the Goal 5 of the Objectives of Development of the Millennium of UN, which consists of the reduction of the mortality in the childhood in 2/3 among the years of 1990 and 2015. The estimates of resources for the attaining of that Goal indicate the need to maintain the investments in water supply, collects of garbage and to increase them in sewer sanitarium. As logical consequence of the reasoning and of the analyses contained in the work, it is suggested as allocation criterion in the planning of resources for amplification of the provision of urban services of sanitation the mortality in the childhood.